The Variable Vector Countermeasure Suit (V2Suit) for space habitation and exploration - Duda, Kevin R.; Vasquez, Rebecca A.; Middleton, Akil J.; Hansberry, Mitchell L.; Newman, Dava J.; Jacobs, Shane E.; West, John J. (Frontiers in Systems Neuroscience, 2015)
The “Variable Vector Countermeasure Suit (V2Suit) for Space Habitation and Exploration” is a novel system concept that provides a platform for integrating sensors and actuators with daily astronaut intravehicular activities to improve health and performance, while reducing the mass and volume of the physiologic adaptation countermeasure systems, as well as the required exercise time during long-duration space exploration missions. The V2Suit system leverages wearable kinematic monitoring technology and uses inertial measurement units (IMUs) and control moment gyroscopes (CMGs) within miniaturized modules placed on body segments to provide a “viscous resistance” during movements against a specified direction of “down” – initially as a countermeasure to the sensorimotor adaptation performance decrements that manifest themselves while living and working in microgravity and during gravitational transitions during long-duration spaceflight, including post-flight recovery and rehabilitation. Several aspects of the V2Suit system concept were explored and simulated prior to developing a brassboard prototype for technology demonstration. This included a system architecture for identifying the key components and their interconnects, initial identification of key human-system integration challenges, development of a simulation architecture for CMG selection and parameter sizing, and the detailed mechanical design and fabrication of a module. The brassboard prototype demonstrates closed-loop control from “down” initialization through CMG actuation, and provides a research platform for human performance evaluations to mitigate sensorimotor adaptation, as well as a tool for determining the performance requirements when used as a musculoskeletal deconditioning countermeasure. This type of countermeasure system also has Earth benefits, particularly in gait or movement stabilization and rehabilitation.